Features of the Clinical Signs, Changes of the Natriuretic Propeptide (NT-proBNP), Left Ventricular Diastolic Function and Heart Rate Variability in the Patients with the Stable Angina Pectoris Combined with Thyroid Hypofunction - Shved M.; Prypkhan I. (Львівський клінічний вісник)
Introduction. In the patients with angina pectoris, in case of the iodine deficiency, the metabolism processes, hemodynamics and autonomic regulation can often change. Aim. To find out the peculiarities of the changes of the natriuretic propeptide NTproBNP, diastolic function of the left ventricle and heart rate variability (HRV) in patients with stable angina pectoris in combination with subclinical hypothyroidism. Materials and methods. To understand the features of the clinical signs, the changes of the natriuretic propeptide – NT-proBNP, left ventricular diastolic function and heart rate variability (HRV) in the patients with the stable angina pectoris, combined with subclinical hypothyroidism, 2 groups of the patients were observed: 39 patients with coronary artery disease: stable angina pectoris of II-III functional class (FC) and 44 patients with the stable angina pectoris in combination with subclinical hypothyroidism. In addition to the routine laboratory and instrumental examination methods, the levels of NTproBNP, thyroid stimulating hormone (TSH), triiodothyronine, thyroxine and peroxidase antibody concentrations were determined, also echocardiography, ECG Holter monitoring with providing the heart rate variability testing were performed. Results. The feature of the clinical manifestations of angina pectoris in the patients with the reduced function of the thyroid gland (TG) is frequent attacks of breathlessness and rapid fatigue, meanwhile the anginal pain occurs rarely. Besides, the symptoms of hypothyroidism join and worsen the course of the main disease. The level of the NT-proBNP in the examined patients with angina pectoris and subclinical hypothyroidism is 25,08 ± 0,66 fmol/ml and is significantly higher, compared to the patients with no hypothyroidism (14,24 ± 0,51 fmol/ml) and compared to the control group of the healthy individuals (3,91 ± 0,22 fmol/ml). In the patients with angina pectoris, combined with subclinical hypothyroidism, compared to the patients with isolated stable angina pectoris of the appropriate FC, more pronounced disorders of the left ventricular diastolic dysfunction with more frequent detection of the pseudonormal type are recorded. In the patients with the angina pectoris, combined with subclinical hypothyroidism, the value of TP was 2415,70 ± 37,31 ms2, sympathetic-vagal index was increasing till 2,20 ± 0,04, indicating the decrease of HRV and hypersympathicotonia, meanwhile in the patients with angina pectoris and preserved thyroid function these changes were less pronounced and were 3015,90 ± 38,72 ms2 and 2,07 ± 0,05 respectively. Conclusions. The study of changes of the level of NT-proBNP, the state of cardiohemodynamics and state of autonomic nervous system in patients with angina pectoris in case of iodine deficiency is very important due to the fact that the course of ischemic heart disease is significantly altered – clinical signs of angina are sunken, often symptoms of heart failure are present in the foreground, and this is an important aspect for timely and adequate pathogenetic treatment.